Implementasi Algoritma C4.5 Untuk Memprediksi Penjualan Sepatu Boots Terlaris di Toko Parabellum - Mochamad Kamil; Yustika Erliani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
In the busines world, especially the shoe shop business, a marketing strategy is needed in order to increase product sales. One of the shoe shop businesses is parabellum. The high number of visitors to Parabellum’s online and offlie stores resulted in the stock of boots being sold out, so that when customers looked for a variety og boots, these boots were no longer available. From this problem, the author helps predict by analyzing data processing using a comparison og the C4.5 algorithm, where the C4.5 algorithm is an algorithm, it will have accurate result in predicting shoe sales data at the Prabellum Store.